Draft Annual Plan 1995-96 Volume I Part II National Capital Territory of Delhi - Planning Commission (Planning Commission, 1995)
Health of the people is not only a desirable goal but also an essential investment in Human resources. The National Health Policy reiterated India's Commitment to attain Health For All (HFA) by 2000 AD. Primary health case has been accepted as the main instrument for achieving this goal. Accordingly, a vast network of health case facilities in all areas and location of this Territory have been established.
Planning Department, Govt. of N.C.T. of Delhi